2019
DOI: 10.1101/845081
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spreading of a mycobacterial cell surface lipid into host epithelial membranes promotes infectivity

Abstract: ABSTRACTSeveral virulence lipids populate the outer cell wall of pathogenic mycobacteria (Jackson, 2014). Phthiocerol dimycocerosate (PDIM), one of the most abundant outer membrane lipids (Anderson, 1929), plays important roles in both defending against host antimicrobial programs (Camacho et al., 2001; Cox et al., 1999; Murry et al., 2009) and in evading these programs altogether (Cambier et al., 2014a; Rousseau et al., 2004). Immediately following infection, mycobacteria rely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Supporting this hypothesis, multiple groups have observed that loss of PDIM reduces phagosomal permeabilization in M. tuberculosis [23][24][25][26]. As the study of M. marinum has provided new insights into PDIM's role in pathogenesis [4,7], we set out to determine if this PDIM-ESX-1 interaction was conserved in M. marinum. In this paper, we confirm that as in M. tuberculosis, proper PDIM localization is required for M. marinum to effectively permeabilize macrophage phagosomes.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Supporting this hypothesis, multiple groups have observed that loss of PDIM reduces phagosomal permeabilization in M. tuberculosis [23][24][25][26]. As the study of M. marinum has provided new insights into PDIM's role in pathogenesis [4,7], we set out to determine if this PDIM-ESX-1 interaction was conserved in M. marinum. In this paper, we confirm that as in M. tuberculosis, proper PDIM localization is required for M. marinum to effectively permeabilize macrophage phagosomes.…”
Section: Introductionmentioning
confidence: 94%
“…PDIM-deficient mutants in M. marinum and M. tuberculosis are attenuated in animal models of infection [2][3][4] and membrane permeability [5,6]. Contact between mycobacteria and host environment results in the transfer of surface PDIM into host membranes, suppressing toll-like receptor signaling (TLR) and preventing the recruitment of microbicidal monocytes during infection [4,7,8]. Consequently, PDIM mutants are rapidly phagocytosed and killed by microbicidal monocytes [4].…”
Section: Introductionmentioning
confidence: 99%
“…PDIM, another major virulence lipid of Mtb, was found in macrophages membranes during infection (Augenstreich et al, 2019). Preliminary results on Mm coating with fluorescent modified PDIM indicated a transfer and a diffusion of these lipids upon contact with macrophages (Cambier et al, 2020). These results also support a passive transfer of PDIM upon contact of the bacteria with host cells.…”
Section: Passive Release Of Mtb Lipidsmentioning
confidence: 69%
“…Supporting this hypothesis, multiple groups have observed that loss of PDIM reduces phagosomal permeabilization in M. tuberculosis [2326]. As the study of M. marinum has provided new insights into PDIM’s role in pathogenesis[4,7], we set out to determine if this PDIM-ESX-1 interaction was conserved in M. marinum . In this paper, we confirm that as in M. tuberculosis , proper PDIM localization is required for M. marinum to effectively permeabilize macrophage phagosomes.…”
Section: Introductionmentioning
confidence: 95%
“…PDIM-deficient mutants in M. marinum and M. tuberculosis are attenuated in animal models of infection[24] and membrane permeability[5,6]. Contact between mycobacteria and host environment results in the transfer of surface PDIM into host membranes, suppressing toll-like receptor signaling (TLR) and preventing the recruitment of microbicidal monocytes during infection[4,7,8]. Consequently, PDIM mutants are rapidly phagocytosed and killed by microbicidal monocytes[4].…”
Section: Introductionmentioning
confidence: 99%